Significance of melt-fraction in HVOF sprayed hydroxyapatite particles, splats and coatings - Khor, Khiam Aik (2012)
Microstructure characterization and property evaluation of high velocity oxy-fuel (HVOF) sprayed hydroxyapatite (HA) splats and coatings were conducted in the present study as a function of the proportion of melting that occurred in HA particles during HVOF spray. In vitro behavior of single and folded HA splats in simulated body fluid was also investigated. Results showed that phase composition of as-sprayed HA coatings was influenced significantly by the melt fraction in HVOF sprayed particles. Melt fraction of the HA powders were experimentally determined from particle morphology analysis. It was found that the spray parameters and starting powder size influenced the melt fraction of the particles. In vitro investigation of individual HA splats made from different HA particles revealed decisive role of local phase composition in influencing their dissolution/precipitation behavior during the test. Furthermore, Raman spectroscopy qualitative inspection on the sprayed HA particles (partial melted) revealed that thermal decomposition occurred within the melted part rather than the unmelted zone. Young's modulus and micro-hardness of the as-sprayed particles and coatings were determined using nano-indentation technique. The resolidified zone of the sprayed HA particles exhibited an average Young's modulus value of 41.25 GPa. The measured values ranged from 23.1 to 65.3 GPa. The unmelted part of the HA powders showed a markedly narrower range. Young's modulus value of 83.9 GPa (±9.4 GPa) was recorded for this region. This succinctly highlight the difference between the unmelted region and melted regions of a HA particle. Young's moduli values measured on HVOF coatings were found to mirror the trend found in the spheroidised particles and splats with apt fidelity.